THE DOMESTICATION OF GENRE. NAJÎB MAHFÛZ AND THE WESTERN NOVEL - Hamarneh, Walid (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1991)
An account of the ways in which Mahfûz domesticates the generic conventions of the Western novel in the Egyptian context. Survey of the writings of Mahfûz.